Prevalence of chronic wet cough and protracted bacterial bronchitis in Aboriginal children - Pamela Laird; James Totterdell; Roz Walker; Anne B. Chang; André Schultz (ERJ Open Research, 2019)
Background Chronic wet cough, the most common symptom of a disease spectrum that encompasses protracted bacterial bronchitis (PBB) and bronchiectasis, is common among Aboriginal children. In the absence of any community prevalence data, and with the high burden of respiratory disease and the European Respiratory Society task force's recommendation to identify disease burden, we determined the prevalence of chronic wet cough and PBB in young Aboriginal children in four remote communities in north Western Australia. Methods A whole-population, prospective study was conducted. Aboriginal children aged ≤7 years were clinically assessed for chronic wet cough by paediatric respiratory clinicians between July 2018 and May 2019. Where children had a wet cough but parents reported a short or uncertain cough duration, children were followed up 1 month later. A medical record audit 6 weeks to 3 months later was used to determine those children with chronic wet cough who had PBB (based on response to antibiotics). Results Of the 203 children, 191 (94%; median age 3.5 years, range 0–7 years) were enrolled. At the initial visit, chronic wet cough was present in 21 (11%), absent in 143 (75%) and unknown in 27 (14%). By follow-up, the total prevalence of chronic wet cough was 13% (95% CI 8–19%) and 10% (95% CI 7–17%) for PBB. Chronic wet cough was more common in the two communities with unsealed roads (19%) compared to the two with sealed roads (7%). Conclusion Given the relatively high prevalence, strategies to address reasons for and treatment of chronic wet cough and PBB in young Aboriginal children in remote north Western Australia are required.